PENGARUH PRAKTIK KERJA INDUSTRI DAN HASIL BELAJAR KEWIRAUSAHAAN TERHADAP MINAT KEWIRAUSAHAAN SISWA KELAS XII SMK NEGERI 1 MENTERADO - (F10211047), Sudianto; ., Herkulana; Sastrawan, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
A common problem in this study is "What is the effect of industrial work practices of entrepreneurship and entrepreneurial learning outcomes of the students' interest in entrepreneurship class XII SMK Negeri 1 Monterado Bengkayang?" .The scope of the study is the independent variable is the variable entrepreneurial industry work practices (Â entrepreneurial learning outcomes (Â Â The dependent variable in this study is the interest in entrepreneurship class XII students of SMK Negeri 1. Data collection tool was questionnaire and data analysis tools is to use a simple regression with using SPSS. The result of this research is the application of industry working practices affect the students' interest in entrepreneurship by 15.8%. It is based on the results of statistical tests on the value of the students' work practices industry t count> t table (3.543> 1.994) and a significant value of 0.001 or less than 0.005.Â  Entrepreneurial learning outcomes affect the students' interest in entrepreneurship. This is based on the results of statistical tests showed that the value of t <t table (-1929 <1.994) and a significant value of 0.058 or more than 0.050Keywords: Industry Employment Practices, Learning Outcomes Entrepreneurship, Entrepreneurship Interests. Â Abstrak: Masalah umum dalam penelitian ini adalah â€œ Apakah pengaruh praktik kerja industri kewirausahaan dan hasil belajar kewirausahaan terhadap minat berwirausaha siswa kelas XII SMK Negeri 1 Monterado Kabupaten Bengkayang?â€Ruang lingkup penelitian adalahÂ  Variabel bebas adalah variabel Praktik kerja industri kewirausahaan (Hasil belajar kewirausahaan (Â Variabel terikat dalam penelitian ini adalah minat berwirausaha siswa kelas XII SMK Negeri 1 Monterado Kabupaten Bengkayang Alat pengumpul datanya angket dan alat analisis datanya menggunakan regresi sederhana dengan bantuan program SPSS.Hasil Penelitian ini adalah penerapan praktik kerja industri berpengaruh terhadap minat berwirausaha siswa sebesar 15,8%. Hasil uji statistik terhadap nilai praktik kerja industri siswa yakni nilai t hitung > t tabel (3,543 > 1,994) dan nilai signifikansi 0,001 atau kurang dari 0,005. Hasil belajar wirausaha berpengaruh terhadap minat berwirausaha . Hasil uji statistik yang menunjukkan bahwa nilai t hitung < t tabel (-1929 < 1,994) dan nilai signifikansi 0,058 atau lebih dari 0,050. Kata kunci: Praktik Kerja Industri, Hasil Belajardan minat Kewirausahaan